A prospective health impact assessment of the international astronomy and space exploration centre. Issue 6 (1st June 2001) - Winters, L Y
Abstract : STUDY OBJECTIVES: Assess the potential health impacts of the proposed International Astronomy and Space Exploration Centre on the population of New Wallasey. Contribute to the piloting of health impact assessment methods. DESIGN: Prospective health impact assessment involving brainstorming sessions and individual interviews with key informants and a literature review. SETTING: New Wallasey Single Regeneration Budget 4 area. PARTICIPANTS: Key stakeholders including local residents' groups selected through purposeful snowball sampling. MAIN RESULTS: Recommendations are made that cover issues around: transport and traffic; civic design; security; public safety, employment and training. CONCLUSIONS: Health impact assessment is a useful pragmatic tool for facilitating wide consultation. In particular engaging the local population in the early planning stages of a proposed development, and assisting in highlighting changes to maximise the positive health influences on affected communities.